Fluorescence analysis method for rapidly measuring high-sulfur copper concentrate
By correcting the analysis curves of different elements in high-sulfur copper concentrate, the problems of high difficulty in calibration of analysis lines and large deviations in the analysis results in the prior art are solved, and the accurate determination of the content of different elements in high-sulfur copper concentrate is achieved.
Patent Information
- Application Number
- CN202411901466.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, X-ray fluorescence analysis spectrometry is used to analyze the high-sulfur copper concentrate components, which need to be corrected according to the interference of different elements. The difficulty of calibration of the analysis line leads to a low correlation coefficient, and the analysis results of each element are large in deviation.
By correcting the analysis curves of different elements in high sulfur copper concentrate, the correction is carried out using elements with overlapping spectral lines, including the correction of Cu, Fe, S, SiO2, CaO, Pb, Zn, As, MgO, Al2O3, Sb, Bi, Ni, Sn, F, and Cl elements.
Accurate determination of different elements in high-sulfur copper concentrate is achieved, and the accuracy and reliability of the analysis results are improved.
Smart Images

Figure CN119757433A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of metal element analysis in mining and smelting production, and in particular to a fluorescence analysis method for rapidly determining high-sulfur copper concentrate. Background Art
[0002] At present, most enterprises' incoming raw materials are mainly low-quality and coarse copper materials, accounting for about 60% of the total incoming ore, of which 20% is high-sulfur copper concentrate. X-ray fluorescence analysis spectroscopy has the advantages of fast analysis speed, high detection accuracy, rapid simultaneous detection of multiple analysis items, good method reproducibility and high precision.
[0003] In the prior art, X-ray fluorescence analysis spectroscopy is used to analyze the composition of high-sulfur copper concentrate, which needs to be corrected according to the interference of different elements. The difficulty of analysis line correction leads to a low correlation coefficient and a large deviation in the analysis results of each element. Therefore, it is necessary to provide an accurate high-sulfur copper concentrate composition analysis method. Summary of the invention
[0004] In order to solve or partially solve the problems existing in the related art, the present application provides a fluorescence analysis method for quickly determining high-sulfur copper concentrate. The fluorescence analysis method can accurately determine the content of Cu, Fe, S, SiO2, CaO, Pb, Zn, As, MgO, Al2O3, Sb, Bi, Ni, Sn, F, and Cl elements in high-sulfur copper concentrate.
[0005] The present application provides a fluorescence analysis method for rapidly determining high-sulfur copper concentrate, comprising the following steps:
[0006] 1) Preparing a high-sulfur copper concentrate sample: mixing high-sulfur copper concentrates with similar element grades to obtain a high-sulfur copper concentrate sample;
[0007] 2) Grinding and screening of high-sulfur copper concentrate samples: Pour the high-sulfur copper concentrate sample into the cleaned grinding disc, grind it and then screen it through a standard sieve;
[0008] 3) Chemical determination: Chemical analysis and determination of the ground and screened high-sulfur copper concentrate samples;
[0009] 4) Preparing a powdered tablet high-sulfur copper concentrate sample: loading the ground and sieved high-sulfur copper concentrate sample into a PVC sample ring, and pressing the ground and sieved high-sulfur copper concentrate sample into a powdered tablet high-sulfur copper concentrate sample;
[0010] 5) X-ray fluorescence spectrometer condition settings;
[0011] 6) Establishing analysis curves of each element: performing element fluorescence analysis intensity test on the powder pressed high-sulfur copper concentrate sample according to the conditions set in step 5), and establishing an analysis curve with element concentration as the abscissa and fluorescence analysis intensity as the ordinate;
[0012] The Cu element is corrected by Fe and SiO2, whose spectral lines overlap.
[0013] The Fe element was corrected using S, Pb, MgO, As and Cu elements with overlapping spectral lines;
[0014] The S element was corrected using Cu, Fe, MgO and CaO, which have overlapping spectral lines.
[0015] The Zn element was corrected by Pb and SiO2, whose spectral lines overlapped;
[0016] The As element is corrected by the S element which has spectral line overlap;
[0017] Al2O3 is corrected by Cu element which has spectral line overlap;
[0018] The Sb element is corrected by using Bi and As elements with overlapping spectral lines;
[0019] The Sn element is corrected by using Sb, SiO2 and Zn elements with overlapping spectral lines;
[0020] The F element is corrected by SiO2 and MgO, which have overlapping spectral lines.
[0021] The Cl element was corrected using the F element, MgO and Pb elements whose spectral lines overlapped.
[0022] 7) Testing the high-sulfur copper concentrate sample: Use an X-ray fluorescence spectrometer to test the high-sulfur copper concentrate sample, measure the fluorescence analysis intensity of each element, and obtain the content of each element according to the analysis curve in step 6).
[0023] Optionally, the mixing time in step 1) is 30-60s.
[0024] Optionally, in step 2), the cleaning is performed once with quartz sand and twice with the copper concentrate sample before grinding.
[0025] Optionally, in step 2), the grinding time is 20 seconds; and the standard sieve is 180 mesh.
[0026] Optionally, in step 4), the diameter of the sample ring is 40*34*4; the pressure of the pressing machine is 35 tons, and the holding time is 10 seconds.
[0027] Optionally, the weight of the high-sulfur copper concentrate sample in step 1) is 200 g.
[0028] The technical solution provided by this application may have the following beneficial effects:
[0029] In the prior art, since the interference of different elements in the high-sulfur copper concentrate needs to be corrected, the difficulty of analytical line correction leads to a low correlation coefficient, and therefore the content of different elements in the high-sulfur copper concentrate is not accurately determined.
[0030] In the present application, by correcting the analysis curves of different elements in the high-sulfur copper concentrate, the Cu element is corrected by the Fe element and SiO2 with overlapping spectral lines, the Fe element is corrected by the S element, Pb element, MgO, As element and Cu element with overlapping spectral lines, the S element is corrected by the Cu element, Fe element, MgO and CaO with overlapping spectral lines, the Zn element is corrected by the Pb element and SiO2 with overlapping spectral lines, the As element is corrected by the S element with overlapping spectral lines, the Al2O3 is corrected by the Cu element with overlapping spectral lines, the Sb element is corrected by the Bi element and As element with overlapping spectral lines, the Sn element is corrected by the Sb element, SiO2 and Zn element with overlapping spectral lines, the F element is corrected by SiO2 and MgO with overlapping spectral lines, and the Cl element is corrected by the F element, MgO and Pb element with overlapping spectral lines, so that the content of different elements in the high-sulfur copper concentrate can be accurately determined.
[0031] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The above and other objects, features and advantages of the present application will become more apparent through a more detailed description of exemplary embodiments of the present application in conjunction with the accompanying drawings, wherein the same reference numerals generally represent the same components in the exemplary embodiments of the present application.
[0033] Figure 1 This is a schematic diagram of the Cu element analysis curve of the high-sulfur copper concentrate sample shown in Example 1 of the present application;
[0034] Figure 2 This is a schematic diagram of the Fe element analysis curve of the high-sulfur copper concentrate sample shown in Example 1 of the present application;
[0035] Figure 3 This is a schematic diagram of the S element analysis curve of the high-sulfur copper concentrate sample shown in Example 1 of the present application;
[0036] Figure 4 This is a schematic diagram of the SiO2 elemental analysis curve of the high-sulfur copper concentrate sample shown in Example 1 of the present application;
[0037] Figure 5This is a schematic diagram of the CaO element analysis curve of the high-sulfur copper concentrate sample shown in Example 1 of the present application;
[0038] Figure 6 This is a schematic diagram of the Pb element analysis curve of the high-sulfur copper concentrate sample shown in Example 1 of the present application;
[0039] Figure 7 This is a schematic diagram of the Zn element analysis curve of the high-sulfur copper concentrate sample shown in Example 1 of the present application;
[0040] Figure 8 This is a schematic diagram of the As element analysis curve of the high-sulfur copper concentrate sample shown in Example 1 of the present application;
[0041] Fig. 9 This is a schematic diagram of the MgO element analysis curve of the high-sulfur copper concentrate sample shown in Example 1 of the present application;
[0042] Fig.10 This is a schematic diagram of the Al2O3 element analysis curve of the high-sulfur copper concentrate sample shown in Example 1 of the present application;
[0043] Fig.11 This is a schematic diagram of the Sb element analysis curve of the high-sulfur copper concentrate sample shown in Example 1 of the present application;
[0044] Fig.12 This is a schematic diagram of the Bi element analysis curve of the high-sulfur copper concentrate sample shown in Example 1 of the present application;
[0045] Fig.13 This is a schematic diagram of the Ni element analysis curve of the high-sulfur copper concentrate sample shown in Example 1 of the present application;
[0046] Fig.14 This is a schematic diagram of the Sn element analysis curve of the high-sulfur copper concentrate sample shown in Example 1 of the present application;
[0047] Fig.15 This is a schematic diagram of the element analysis curve of the high-sulfur copper concentrate sample F shown in Example 1 of the present application;
[0048] Fig.16 It is a schematic diagram of the Cl element analysis curve of the high-sulfur copper concentrate sample shown in Example 1 of the present application. DETAILED DESCRIPTION
[0049] The embodiments of the present application will be described in more detail below with reference to the accompanying drawings. Although the embodiments of the present application are shown in the accompanying drawings, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to make the present application more thorough and complete, and to fully convey the scope of the present application to those skilled in the art.
[0050] Example 1
[0051] The sealed sample preparation pulverizer (for sample grinding and mixing, model: GJ100-1, manufacturer: Lichen Technology), 180 mesh standard sieve (sample screening, sample particle size inspection), 40-ton sample press (powder sample pressing, model: ZHY-401B, manufacturer: Beijing Zhonghe), sample ring (powder sample pressing mold, X-ray fluorescence spectrometer (including data processing software, model: ZETIUM (PW5400) manufacturer: PANalytical, the Netherlands) and other instruments and equipment tools are used. The detailed operation steps of the analysis method are as follows:
[0052] 1. Preparation of high-sulfur copper concentrate samples
[0053] The chemical analysis grade of the high-sulfur copper concentrate is statistically performed, and the grades of the main elements of copper, iron, sulfur, and arsenic are arranged from low to high. The high-sulfur copper concentrate with similar element grades is poured onto a mixing cloth. The mixing time is 30-60s, and the high-sulfur copper concentrate samples are prepared by mixing. The weight of each high-sulfur copper concentrate sample is 200g-300g.
[0054] 2. Grinding and screening of high-sulfur copper concentrate samples
[0055] The grinding disc is cleaned once with quartz sand and cleaned twice with the high-sulfur copper concentrate sample before grinding. The remaining high-sulfur copper concentrate sample is poured into the cleaned grinding disc. The grinding time is set to 20s each time. The ground high-sulfur copper concentrate sample is sieved with a 180-mesh standard sieve. The high-sulfur copper concentrate sample on the sieve that cannot pass the sieve is mixed with the unground high-sulfur copper concentrate sample and continues to be ground until all the high-sulfur copper concentrate samples pass the 180-mesh sieve.
[0056] 3. Chemical value
[0057] Chemical analysis and determination of Cu, Fe, S, SiO2, CaO, Pb, Zn, As, MgO, Al2O3, Sb, Bi, Ni, Sn, F and Cl elements in the ground and screened high-sulfur copper concentrate samples.
[0058] 4. Preparation of powder tablet high sulfur copper concentrate sample
[0059] The ground and sieved high-sulfur copper concentrate samples were loaded into a PVC sample ring with a diameter of 40*34*4; the pressure of the sample press was set to 35 tons and the pressure holding time was 10s, and the ground and sieved high-sulfur copper concentrate samples were pressed into powdered pressed high-sulfur copper concentrate samples.
[0060] 5. X-ray fluorescence spectrometer condition settings
[0061] Set the fluorescence analysis conditions for each element as follows:
[0062]
[0063] 6. Establish analysis curves for each element
[0064] According to the conditions set in step 5), the element fluorescence analysis intensity test is performed on the powder pressed high-sulfur copper concentrate sample, and an analysis curve is established with element concentration as the horizontal axis and fluorescence analysis intensity as the vertical axis (fluorescence analysis quantitative analysis, element X-ray fluorescence analysis light intensity is linearly related to chemical concentration). By deleting the data points on the curve, the linear correlation coefficient of the fluorescence analysis curve of each element is controlled to be above 0.995, and each analysis element curve is established and corrected one by one according to the above method.
[0065] Cu element curve establishment and correction: the analysis curve was established with element concentration as the horizontal axis and fluorescence analysis intensity as the vertical axis. Two measurement channels, Cu and Cu1, were used. The Cu measurement channel used two spectral lines, kα1 and kα2. The interfering elements Fe and SiO2 with overlapping spectral lines were added for correction. The Fe correction coefficient of 0.18164 and the SiO2 correction coefficient of -0.54399 were calculated. After locking the coefficients, the curve was calibrated and the points deviating from the curve were deleted. The Cu1 measurement channel used two spectral lines, kα1 and kα2. The interfering elements Fe and SiO2 with overlapping spectral lines were added for correction. The Fe correction coefficient of 0.18020 and the SiO2 correction coefficient of -0.54146 were calculated. After locking the coefficients, the curve was calibrated and the points deviating from the curve were deleted.
[0066] Establishment and correction of Fe element curve: establish the analysis curve with element concentration as the horizontal axis and fluorescence analysis intensity as the vertical axis. Use the two spectral lines kα1 and kα2, add the interfering elements S, Pb, MgO, As, and Cu with overlapping spectral lines for correction. The S correction coefficient is -0.025043, Pb correction coefficient is 0.37371, MgO correction coefficient is -2.0385, As correction coefficient is 4.9537 and Cu correction coefficient is 0.057037. After locking the coefficients, calibrate the curve and delete the points that deviate from the curve.
[0067] Establishment and correction of S element curve: establish the analysis curve with element concentration as the horizontal axis and fluorescence analysis intensity as the vertical axis. Use the two spectral lines kα1 and kα2, add the interfering elements Cu, Fe, MgO and CaO with overlapping spectral lines for correction. The correction coefficients of Cu, Fe, MgO and CaO are calculated to be 0.24164, -0.42447, -3.6716 and 2.6132, lock the coefficients and calibrate the curve, and delete the points that deviate from the curve.
[0068] Establishment and correction of SiO2 element curve: establish the analysis curve with element concentration as the horizontal axis and fluorescence analysis intensity as the vertical axis, use two spectral lines, kα1 and kα2, and delete the points that deviate from the curve.
[0069] CaO element curve establishment and correction: establish the analysis curve with element concentration as the horizontal axis and fluorescence analysis intensity as the vertical axis, use the two spectral lines kα1 and kα2, and delete the points that deviate from the curve.
[0070] Establishment and correction of Pb element curve: establish the analysis curve with element concentration as the horizontal axis and fluorescence analysis intensity as the vertical axis, use Lβ1 spectrum line, and delete the points that deviate from the curve.
[0071] Establishment and correction of Zn element curve: The analysis curve was established with element concentration as the horizontal axis and fluorescence analysis intensity as the vertical axis. Two measurement channels, Zn and Zn1, were used. The Zn channel used two spectral lines, kα1 and kα2, and the interfering element Pb with overlapping spectral lines was added for correction. The Pb correction coefficient of -1.1400 was calculated. After locking the coefficient, the curve was calibrated and the points deviating from the curve were deleted. The Zn1 channel used two spectral lines, kβ1 and kβ3, and the interfering elements Pb and SiO2 with overlapping spectral lines were added for correction. The Pb correction coefficient of -1.3389 and the SiO2 coefficient of 0.031127 were calculated. After locking the coefficient, the curve was calibrated and the points deviating from the curve were deleted.
[0072] Establishment and correction of As element curve: establish the analysis curve with element concentration as the horizontal axis and fluorescence analysis intensity as the vertical axis. Use two spectral lines, kβ1 and kβ3, add the interfering element S correction with overlapping spectral lines, calculate the S correction coefficient -0.00092799, lock the coefficient and calibrate the curve, and delete the points that deviate from the curve.
[0073] MgO element curve establishment and correction: establish the analysis curve with element concentration as the horizontal axis and fluorescence analysis intensity as the vertical axis, use the two spectral lines kα1 and kα2, and delete the points that deviate from the curve.
[0074] Al2O3 element curve establishment and correction: The analysis curve was established with element concentration as the horizontal axis and fluorescence analysis intensity as the vertical axis. The two spectral lines kα1 and kα2 were used, and the interfering element Cu with overlapping spectral lines was added for correction. The Cu correction coefficient of -0.036834 was calculated. After locking the coefficient, the curve was calibrated and the points deviating from the curve were deleted.
[0075] Establishment and correction of Sb element curve: establish the analysis curve with element concentration as the horizontal axis and fluorescence analysis intensity as the vertical axis. Use the two spectral lines kα1 and kα2, add the interfering elements Bi and As with overlapping spectral lines for correction, calculate the Bi correction coefficient of 0.46928 and the As correction coefficient of -0.10524, calibrate the curve and delete the points that deviate from the curve.
[0076] Bi element curve establishment and correction: establish the analysis curve with element concentration as the horizontal axis and fluorescence analysis intensity as the vertical axis, use the two spectral lines Lα1 and Lα2, and delete the points that deviate from the curve.
[0077] Establishment and correction of Ni element curve: establish the analysis curve with element concentration as the horizontal axis and fluorescence analysis intensity as the vertical axis, use two spectral lines, kα1 and kα2, and delete the points that deviate from the curve.
[0078] Sn element curve establishment and correction: The analysis curve was established with element concentration as the horizontal axis and fluorescence analysis intensity as the vertical axis. The two spectral lines kα1 and kα2 were used, and the interfering elements Sb, SiO2, and Zn with overlapping spectral lines were added for correction. The Sb correction coefficient was 0.033612, the SiO2 correction coefficient was -0.0011719, and the Zn correction coefficient was 0.000061867. The curve was calibrated after locking the coefficients, and the points that deviated from the curve were deleted.
[0079] F element curve establishment and correction: The analysis curve was established with element concentration as the horizontal axis and fluorescence analysis intensity as the vertical axis. The two spectral lines kα1 and kα2 were used, and the interfering elements SiO2 and MgO with overlapping spectral lines were added for correction. The SiO2 correction coefficient was calculated to be -0.0035894 and the MgO correction coefficient was -0.0075472. The curve was calibrated after locking the coefficients, and the points deviating from the curve were deleted.
[0080] Establishment and correction of Cl element curve: establish the analysis curve with element concentration as the horizontal axis and fluorescence analysis intensity as the vertical axis. Use the two spectral lines kα1 and kα2, add the interfering elements F, MgO and Pb with overlapping spectral lines for correction, and calculate the correction coefficient of F -0.013208, MgO correction coefficient 0.0032470 and Pb correction coefficient -0.0019548. After locking the coefficients, calibrate the curve and delete the points that deviate from the curve.
[0081] 7) Testing the high-sulfur copper concentrate sample: Use an X-ray fluorescence spectrometer to test the high-sulfur copper concentrate sample, measure the fluorescence analysis intensity of each element, and obtain the content of each element according to the analysis curve described in step 6).
[0082] Example 2: Reproducibility and precision analysis
[0083] Five groups of high-sulfur copper concentrate samples were used for chemical analysis and fluorescence analysis comparison. Each element analysis curve was checked to see if it met the requirements. The reproducibility and precision of each element were calculated. If the requirements were not met, the analysis curve needed to be readjusted and calibrated. The results are shown in Table 5.
[0084] Table 5 Comparison between X-ray fluorescence spectrometry and chemical method (%)
[0085]
[0086] The experiment was repeated using a set of high-sulfur copper concentrate samples, and the results are shown in Table 6.
[0087] Table 6 Precision test results (n = 10)
[0088]
[0089] It can be seen from Tables 5 and 6 that there is no significant difference between the chemical analysis and the fluorescence analysis method of the present application, and the fluorescence analysis method of the present application has good reproducibility and precision.
[0090] The embodiments of the present application have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. A fluorescence analysis method for rapid determination of high-sulfur copper concentrate, characterized in that: The following steps are involved: 1) Preparing a high-sulfur copper concentrate sample: mixing high-sulfur copper concentrates with similar element grades to obtain a high-sulfur copper concentrate sample; 2) Grinding and screening of high-sulfur copper concentrate samples: Pour the high-sulfur copper concentrate sample into the cleaned grinding disc, grind it and then screen it through a standard sieve; 3) Chemical determination: Chemical analysis and determination of the ground and screened high-sulfur copper concentrate samples; 4) Preparing a powdered tablet high-sulfur copper concentrate sample: loading the ground and sieved high-sulfur copper concentrate sample into a PVC sample ring, and pressing the ground and sieved high-sulfur copper concentrate sample into a powdered tablet high-sulfur copper concentrate sample; 5) Setting X-ray fluorescence spectrometer conditions; 6) Establishing analysis curves of each element: performing element fluorescence analysis intensity test on the powder pressed high-sulfur copper concentrate sample according to the conditions set in step 5), and establishing an analysis curve with element concentration as the abscissa and fluorescence analysis intensity as the ordinate; The Cu element is corrected by Fe and SiO2, whose spectral lines overlap. The Fe element was corrected using S, Pb, MgO, As and Cu elements with overlapping spectral lines; The S element was corrected using Cu, Fe, MgO and CaO, which have overlapping spectral lines. The Zn element was corrected by Pb and SiO2, whose spectral lines overlapped; The As element is corrected by the S element which has spectral line overlap; Al2O3 is corrected by Cu element which has spectral line overlap; The Sb element is corrected by using Bi and As elements with overlapping spectral lines; The Sn element is corrected by using Sb, SiO2 and Zn elements with overlapping spectral lines; The F element is corrected by SiO2 and MgO, which have overlapping spectral lines. The Cl element was corrected using the F element, MgO and Pb elements whose spectral lines overlapped. 7) Testing the high-sulfur copper concentrate sample: Use an X-ray fluorescence spectrometer to test the high-sulfur copper concentrate sample, measure the fluorescence analysis intensity of each element, and obtain the content of each element according to the analysis curve described in step 6).
2. The fluorescence analysis method according to claim 1, characterized in that The mixing time in step 1) is 30-60s.
3. The fluorescence analysis method according to claim 1, characterized in that In the step 2), the cleaning is performed once with quartz sand and twice with the copper concentrate sample before grinding.
4. The fluorescence analysis method according to claim 1, characterized in that: The grinding time in step 2) is 20 seconds; the standard sieve is 180 mesh.
5. The fluorescence analysis method according to claim 1, characterized in that: In the step 4), the diameter of the sample ring is 40*34*4; the pressure of the pressing machine is 35 tons, and the holding time is 10 seconds.
6. The fluorescence analysis method according to claim 1, characterized in that: The weight of the high-sulfur copper concentrate sample in step 1) is 200 g.
Citation Information
Patent Citations
X-fluorescence joint-measurement analysis method for elements of mixed copper concentrate
CN104880477A
Preparation of high-copper-content converter oxidizing slag fluorescence analysis standard sample and multi-element rapid analysis method
CN111610211A
X-ray fluorescence analysis and detection method for element content of copper smelting smoke dust
CN115468971A